MEDIA, TEKNOLOGI DAN MASYARAKAT GENDER & WEBSITE - Goenawan, Felicia (Institute of Research and Community Outreach - Petra Christian University, 2007)
Gender and sexuality have alikeness in biological basis to sex, and both of them are social construction, yet they are different because of being established by different social bases. Gender is also a cultural construction that is open in nature for all of changes. Therefore, the two concepts are frequently misunderstood as if they were the same. The misunderstanding is easily comprehendible, due to discoursing on the two concepts that are really similar to each other have just reverberated in the decade of 90s. Moreover, in the beginning there have not been many social scientists yet that specially examine themes related to gender and sex problems. Even though the writing is very simple and strive to contribute to inceptive exploration on gender and sex concepts in its relatedness to application of Web-site, as a socialization medium.